Dietary selenium nanoparticles alleviate heat stress-induced reproductive impairment in Onychostoma macrolepis, with MeSeCys as a key bioactive selenium species - Chao Zhu; Weiping Pan; Jianbo Zheng; Shili Liu; Meili Chi; Wenping Jiang; Shun Cheng; Junzhi Luo; Wuzi Dong; Zhilong Chen; Fei Li (Theriogenology, 2026)

Restoration of membrane potential rescues organelle function via NS309-mediated KCa activation in aged porcine oocytes - Ying-Yan Jin; Cheng-Lin Zhan; Song-Hee Lee; Ji-Yeon Lee; Xiang-Shun Cui (Theriogenology, 2026)

Research on the interface damage mechanism and energy evolution of concrete under ice pull - Shun Yang; Yuan Qin; Yue Qi; Xianwei Zhang; Xiangnan Cheng (Cold Regions Science and Technology, 2026)

Low-cost, energy-efficient sap flow system reveals multi-year transpiration dynamics in a subtropical mixed-species plantation - Ignacio Ruiz de la Cuesta Vela; Tomonori Kume; Cheng-Wei Lai; Man-Shun Hsu; Chieh-Yu Hong; Shin-Min Chong; Shih-Chieh Chang (Agricultural and Forest Meteorology, 2026)

Corrigendum to “A case study of Lepiota brunneoincarnata poisoning with endoscopic nasobiliary drainage in Shandong, China” [Toxicon 161C (2019) 12-16] - Jian Sun; Hong-Shun Zhang; Hai-Jiao Li; Yi-Zhe Zhang; Qian He; Jun-Jia Lu; Yu Yin; Cheng-Ye Sun (Toxicon, 2026)

Unraveling the modulating mechanism of Maillard reaction gradients on structural properties and emulsifying stabilization of Prunus mume melanoidins - Wen-zhang Qian; Yi-xiao Xiao; Shou-wei Yin; Ji-cheng Chen; Jin-lin Guo; Shun Gao (Food Chemistry, 2026)

Integrating the machine learning framework to decipher ozone control strategies in coastal regions: From seasonal management to source interaction effects - Yan Tan; Yujia Zhang; Fangxiao Du; Yifan Wang; Likun Xue; Yi Chen; Linyang Zhang; Zizhen Ma; Shun-cheng Lee; Yu Huang (Environmental Pollution, 2026)

Analysis of the effect of local scour on pile-soil interaction in marine pile foundation - Zhang Xiao-ling; Guo Xiao-zheng; Li Xu-zhe; Xu Cheng-shun (Coastal Engineering, 2026)

Functional characterization of the Cbr1 gene in regulating alkaline tolerance in grass carp - Jianbo Zheng; Yi Xu; Qi Chen; Fei Li; Shili Liu; Chao Zhu; Shun Cheng; Wenping Jiang; Meili Chi; Junzhi Luo; Caiyan Li; Xiaohui Xu; et al. (Aquaculture, 2026)

The UL31 protein of duck plague virus promotes viral replication and interacts with ICP4, ICP22, and VP16 proteins. - Hongying Chen; Anchun Cheng; Huijun Cao; Mingshu Wang; Qiao Yang; Xumin Ou; Di Sun; Bin Tian; Yu He; Zhen Wu; Juan Huang; Ying Wu; et al. (Veterinary Microbiology, 2026)

Correction: YAP regulates porcine skin-derived stem cells self-renewal partly by repressing Wnt/β-catenin signaling pathway - Hong-Chen Yan; Yu Sun; Ming-Yu Zhang; Shu-Er Zhang; Jia-Dong Sun; Paul W. Dyce; Francesca Gioia Klinger; Massimo De Felici; Wei Shen; Shun-Feng Cheng (Histochemistry and Cell Biology, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

T-ResUNet: A deep-learning framework for spatiotemporal prediction of granular–fluid dam-break flows - Cheng-ming Lei; Shun Wang; Xuan Kang; Zheng-yang Su; Wei Wu (Journal of Hydrology, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Bacillus velezensis-fermented postbiotics as feed additives for viral infection control in largemouth bass (Micropterus salmoides) - Gaofeng Cheng; Zhihao Jiang; Shun Li; Ruiqi Lin; Xinyou Wang; Yong Shi; Xiaoyun Chen; Zhen Xu; Weiguang Kong (Fish & Shellfish Immunology, 2026)

Immunoglobulin M response in different intestinal segments of largemouth bass (Micropterus salmoides) following largemouth bass virus (LMBV) infection - Xinyou Wang; Gaofeng Cheng; Jie Sun; Chang Cai; Zhihao Jiang; Ruiqi Lin; Shun Li; Li Li; Juan Zhao; Zhen Xu; Weiguang Kong (Fish & Shellfish Immunology, 2026)

Precise engineering of atomic sites on carbon nitride for carbon dioxide photoreduction from single-atom to multi-atom: a review - Leting Yang; Xianjin Shi; Hongna Zhang; Yu Huang; Jiaquan Zhang; Shun-cheng Lee (Environmental Chemistry Letters, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Sourness signature during Prunus mume fruit development: Integrative insight from metabolomics, organic acid profiles, E-tongue, and computational binding simulation - Shun Gao; Yun-yi Hu; Wen-zhang Qian; Yi-xiao Xiao; Jia-li Liao; Ji-cheng Chen (Food Chemistry, 2026)

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Computational method of pile-soil interaction for offshore pile foundations considering scour effects - Xiao-ling Zhang; Xiao-zheng Guo; Pi-guang Wang; Cheng-shun Xu (Ocean Engineering, 2026)

Flowering dynamics of plant individual and population under increased planting density and its association with yield formation in maize - Zhi-Wei Wang; Cheng Huang; Zhen-Yuan Chen; Bo Hong; Yu-Tong Zhou; Xiao-Gui Liang; Xian-Min Chen; Shun-Li Zhou; Si Shen (Field Crops Research, 2026)

Impact of NOx titration on nighttime isoprene in coastal South China: Preserving ozone precursors via suppressed oxidation - Yan Tan; Yujia Zhang; Yifan Wang; Yi Chen; Tao Wang; Zizhen Ma; Linyang Zhang; Meng Wang; Shun-cheng Lee (Environmental Research, 2026)

Oncogenic overexpression of kallikrein-related peptidase 7 is associated with the progression of thyroid cancer - Shun-Yu Chi; Chi-Yu Kuo; Shih-Yuan Huang; Shih-Ping Cheng (Histochemistry and Cell Biology, 2026)

Hydrology and sediment supply in the largest lake system of Qaidam Basin, northeastern Qinghai-Xizang Plateau: insights from surface-sediment grain size - Hongyu Li; Haicheng Wei; Aiying Cheng; Chunliang Gao; Chenyu Wang; Ronglei Duan; Shun Wang; Hongpan Xue (Journal of Oceanology and Limnology, 2026)

Functional characterization of NuoB and SdhC subunits of respiratory complexes in antibiotic resistance and pathogenicity of Riemerella anatipestifer - Mengying Wang; Chen Xiang; Mingshu Wang; Dekang Zhu; Renyong Jia; Shun Chen; Xinxin Zhao; Ying Wu; Qiao Yang; Shaqiu Zhang; Bin Tian; Juan Huang; et al. (Veterinary Microbiology, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Development of a sex-linked PCR marker for non-invasive and early sex determination in largemouth bass (Micropterus salmoides) - Fei Li; Jianbo Zheng; Shili Liu; Shun Cheng; Wenping Jiang; Meili Chi; Chao Zhu; Miao Peng; Qinghui Meng (Conservation Genetics Resources, 2026)

Experimental study on dynamic response of offshore wind turbine structures under asymmetric wave and wind loads - Zhang Xiao-ling; Zhou Guang-li; Zhang Bing-jie; Xu Cheng-shun (Ocean Engineering, 2026)

Advances in Calotropis gigantea Linn.: from phytochemistry and biological activities to diverse applications - Guo-Qing Chen; Xin-Ying Wu; Yun-Cheng Huang; Jian-Ming Jiang; Shun-Yuan Guo; Jia-Hong Chen; Zhen-Dan He; Xun Song (Next Research, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Combined benefits of multi-hazard early warnings on human mobility resilience to tropical cyclones - Haiyan Liu; Jianghao Wang; Zhifeng Cheng; Siqin Wang; Laurence Hawker; Jiatong Han; Phil J. Ashworth; Steve Darby; Faith Ka Shun Chan; Jian Liu; Andrew J. Tatem; Shengjie Lai (Global Environmental Change, 2026)

Understanding bioactivity-related significance of germination on crude polysaccharides and their purified fractions from black soybean: A study of their biochemical characteristics - Chien-Cheng Yeh; Meng-I Kuo; Ai-Lien Lee; Yung-Shun Ma; Chun-Ping Lu (Food Chemistry, 2026)

Surface-displayed MCP-3 vaccine in Bacillus subtilis elicits protective immune responses against LMBV infection in largemouth bass - Ruiqi Lin; Zhihao Jiang; Qianqian Zhang; Shun Li; Xueying Qin; Xinyou Wang; Gaofeng Cheng; Zhen Xu; Weiguang Kong (Fish & Shellfish Immunology, 2026)

S-scheme polyphenylguanidine / 2D-Bi2WO6 heterojunction photocatalytic composite membrane: H2 production and Congo red degradation - Tian Xu; Dongqing Liu; Bowen Lv; Shun Zhou; Yuxuan Cheng; Qinxing Xie; Yongzhu Zhou; Xingyi Lu (Journal of Environmental Management, 2026)

Structural diversity of Ym2, a gene conferring resistance against Wheat yellow mosaic virus - Wenjing Xu; Xiaoyi Xu; Kohei Mishina; Youko Oono; Shun Sakuma; Mohammad Pourkheirandish; Assaf Distelfeld; Xiaoxue Zeng; Xiaolu Wang; Baoqiang Li; Takao Komatsuda; Cheng Liu (Theoretical and Applied Genetics, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

An electrocatalytic dual molecularly imprinted polymer-based biosensor enables femtomolar detection of CD44 without antibodies - Ping Xia; Cheng Chen; Ruifang Bai; Weige Dong; Yuchun Fu; Chungu Zhang; Lianhai Shan; Shun Feng (Analytica Chimica Acta, 2026)

Whole‐Genome Single Nucleotide Polymorphism Analysis and High‐Resolution Melting ( HRM ) Differentiation of Edwardsiella anguillarum and Edwardsiella piscicida - Atiek Rahmawaty; Li Wu Cheng; Jue‐Liang Hsu; Shun Maekawa; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
This study aimed to develop a method to differentiate between two closely related bacterial species within the genus Edwardsiella , namely Edwardsiella anguillarum and Edwardsiella piscicida , which cause Edwardsiellosis in fish aquaculture. Whole‐genome single nucleotide polymorphism (SNP) analysis was conducted to assess the genetic relationships among E. piscicida , E. anguillarum and Edwardsiella ictaluri . SNP distance matrices and phylogenetic trees demonstrated that isolates within each species clustered together, confirming genetic SNP distinctiveness. SNP annotation and distance comparisons identified key genes— artI , dnaK , hlyB , ubiB , hutW , ydgD , MCP and fliC —that exhibited significant divergence. We designed specific primers targeting SNPs in these genes and used these primers for real‐time PCR and High‐Resolution Melting (HRM) analysis. HRM analysis using designed primer pairs revealed distinct melting temperature ( Tm ) peaks for E. anguillarum and E. piscicida . HRM analysis of 37 isolates that were previously identified as E. tarda based on phenotypic characteristics identified them as either E. anguillarum (35) or E. piscicida (2). These results showed that hlyB was the most reliable target gene for distinguishing between E. anguillarum and E. piscicida . The HRM technique is a fast, cost‐effective method for differentiating these closely related bacterial species and provides insights into the genetic variation among different species of Edwardsiella and host‐specific strains.

Fitness-Driven Assessment of Mooring-System Designs for 15-MW FOWT in Shallow Waters - Shun-Wen Cheng; Nai-Chi Chen; Cheng-Hsien Chung; Ray-Yeng Yang (Journal of Marine Science and Engineering, 2026)
Offshore wind energy is a key enabler of the global net-zero transition. As nearshore fixed-bottom projects reach maturity, floating offshore wind turbines (FOWTs) are becoming the next major focus for large scale deployment. To accelerate this development and reduce construction costs, it is essential to optimize mooring systems through a systematic and performance driven framework. This study focuses on the mooring assessment of the Taiwan-developed DeltaFloat semi-submersible platform supporting a 15 MW turbine at a 70 m water depth offshore Hsinchu, Taiwan. A full-chain catenary mooring system was designed based on site specific metocean conditions. The proposed framework integrates ANSYS AQWA (version 2024 R1) and Orcina OrcaFlex (version 11.5) simulations with sensitivity analyses and performance-based fitness metrics including offset, inclination, and line tension to identify key parameters governing mooring behavior. Additionally, an analysis of variance (ANOVA) was conducted to quantitatively evaluate the statistical significance of each design parameter. Results indicate that mooring line length is the most influential factor affecting system performance, followed by line angle and diameter. Optimizing these parameters significantly improves platform stability and reduces tension loads without excessive material use. Building on the optimized symmetric configuration, an asymmetric mooring concept with unequal line lengths is proposed. The asymmetric layout achieves performance comparable to traditional 3 × 1 and 3 × 2 systems under extreme environmental conditions while demonstrating potential reductions in material use and overall cost. Nevertheless, the unbalanced load distribution highlights the need for multi-scenario validation and fatigue assessment to ensure long-term reliability. Overall, the study establishes a comprehensive and sensitivity-based evaluation framework for floating wind mooring systems. The findings provide a balanced and practical reference for the cost-efficient design of floating offshore wind farms in the Taiwan Strait and other shallow-water regions.

Nobiletin alleviates heat stress-induced meiotic arrest via restoring CDK1 and MAPK activity in porcine oocytes - Jae-Min Sim; Song-Hee Lee; Cheng-Lin Zhan; Qin-Yue Lu; Gyu-Hyun Lee; Hyeon-Ji Song; Yu-Jin Jo; Ji-Su Kim; Eui-Bae Jeung; Xiang-Shun Cui (Theriogenology, 2026)

Dynamic model test of offshore wind turbine structure under different operating conditions - Zhang Bing-jie; Zhang Xiao-ling; Xu Cheng-shun; Du Xiu-li (Ocean Engineering, 2026)

Sustainable high-titer production of β-elemene in Yarrowia lipolytica via modular engineering, pathway refactoring, and a chimeric germacrene A synthase - Shun-Cheng Liu; Longxing Xu; Yuejia Sun; Lei Zhang; Weichen Zhang; Jing Xu; Pengcai Liu; Fan Shi; Faming Tian; Hong Xu; Xiaoming Song; Lijie Yuan; et al. (Chemical Engineering Journal, 2026)

Antibiotic Alternative Strategies Against Aeromonas hydrophila Infections: New Trends and Advances - Shengping Li; Jing Dong; Shun Zhou; Bo Cheng; Xiaohui Ai (Reviews in Aquaculture, 2026)
Aeromonas hydrophila ( A. hydrophila ), an opportunistic pathogen widely distributed in aquatic environments and foods, is a serious threat to aquatic animals and even human health. Driven by the A. hydrophila diseases, various prevention and treatment strategies have gradually emerged. In this study, we reviewed the advances in the prevention and treatment of A. hydrophila diseases, including antibiotics, plant extracts, essential oils, phages, antimicrobial peptides (AMPs), probiotics, vaccines, disinfectants, and combination therapy. Although many prevention and treatment studies have been reported, A. hydrophila infection remains a problem. Therefore, we summarized some reports with significant in vivo therapeutic effects against A. hydrophila infections and provided several suggestions to help translate reported tools into clinical applications, and further predict potential artificial intelligence‐ and synthetic biology‐based prevention and control strategies in the future. As a result, this review provides a reference for the clinical prevention and treatment of A. hydrophila infections and research ideas for researchers in the future.

Room-Temperature Fabrication of Dual-Functional SiO2/TiO2 Coating for Photovoltaic Efficiency Enhancement: From Laboratory Development to Field Validation - Pengge Wang; Xinwei Li; Ning Zhang; Yue Zhai; Zhenyu Wang; Long Cui; Suixin Liu; Wingkei Ho; Yu Huang; Shun-cheng Lee (Aerosol Science and Engineering, 2025)

Dynamic response of offshore wind turbine considering sand stiffness evolution characteristics and scour effect - Zhang Xiao-ling; Hou Xiao-he; Wang Pi-guang; Xu Cheng-shun (Soil Dynamics and Earthquake Engineering, 2025)

Fabrication of Rubus chingii Hu ellagitannins-loaded W/O/W double emulsion gels stabilized by WPI/pectin complexes: Physicochemical properties, digestion characteristics, and transformation of ellagitannins - Dong-Jun Hou; Quan-yuan Xie; Ming-Shun Chen; Yu-Lin Cheng; Bing Zhang; Zong-cai Tu; Lu Zhang (Food Chemistry, 2025)

Host acetyl-CoA pathways support WSSV replication - Shu-Wen Cheng; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Effect of parasite infection on mud shrimp (Austinogebia edulis) in the coast of Taiwan - Yen-Cheng Liang; Tien-Hsuan Lu; Shun-De Yang (Fish & Shellfish Immunology, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Elegance in simplicity: Hollow mesoporous silica inhibits pyraclonil metabolism to boost its herbicidal efficacy on Echinochloa crus-galli - Tangqi Feng; Lan Wu; Tianhong Lei; Wenjing Sun; Jian Wang; Dong Cheng; Li Liu; Pengjia Tang; Wenzhuo Wang; Shun He; Hongju Ma (Chemical Engineering Journal, 2025)

Identifying CSNK1E as a therapeutic target in thyroid cancer among the core circadian clock genes - Shun-Yu Chi; Yi-Chiung Hsu; Chung-Hsin Tsai; Shih-Yuan Huang; Shao-Chiang Chang; Shih-Ping Cheng (Histochemistry and Cell Biology, 2025)

mTORC1 regulates the proliferation of SOX9+ porcine skin-derived stem cells (pSDSCs) by promoting S6K phosphorylation - Ming-Xin Zang; Geng Zhang; Ying Zhang; Sha-Sha Wang; Xiang-Wei Zhai; Na Zhao; Wei Ge; Jin-Wen Xie; Wei Shen; Shun-Feng Cheng (Histochemistry and Cell Biology, 2025)

Two novel species of Hermatomyces (Dothideomycetes) from Fagales in China - Yan-Yan Yang; Tai-Shun Li; Chitrabhanu S. Bhunjun; Vinodhini Thiyagaraja; Darbhe J. Bhat; Shu-Cheng He; Qi Zhao; Fatimah Al-Otibi; Pattana Kakumyan; Kevin D. Hyde (Mycological Progress, 2025)

DPV UL38 stabilizes MFN2 to subvert MAVS-mediated antiviral immunity in ducks - Bin Tian; Xuetong Wang; Shuyi He; Dongjie Cai; Yanming Tian; Mingshu Wang; Renyong Jia; Shun Chen; Dekang Zhu; Mafeng Liu; Ying Wu; Qiao Yang; et al. (Veterinary Microbiology, 2025)

Duck plague virus ICP27 protein suppresses IFN-β production by dual targeting of DNA- and RNA-sensing pathways - Mengya Zhang; Yumei He; Fengchen Jin; Mingshu Wang; Qiao Yang; Renyong Jia; Shun Chen; Bin Tian; Xumin Ou; Juan Huang; Di Sun; Dekang Zhu; et al. (Veterinary Microbiology, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Multi-mechanism ultrasound enhanced macroporous resin flavonoid adsorption/desorption: A green and sustainable process for balancing mass transfer efficiency and reusability - Wen-zhang Qian; Yun-yi Hu; Yi-xiao Xiao; Shao-jun Fan; Shih-Hong Hsu; Tsair-Wang Chung; Ji-cheng Chen; Shun Gao (Chemical Engineering Journal, 2025)

Path Analysis and Multiple Linear Regression Fitting Study on Body Weight and Visceral Organ Mass of Male and Female Ussuri Catfish (Pseudobagras ussuriensis) - Qian Qi; Feng Yang; Xiaohui Sun; Chenran Lv; Shun Shi; Xiang Ding; Liming Zhao; Cheng Zhang (Fishes, 2025)
Pseudobagras ussuriensis is a valuable freshwater fish species with enormous breeding potential. To clarify the relationship between the main visceral indices and body weight in this species, 139 cultured individuals were randomly selected to measure body weight and six major organs (namely the intestine, liver, swim bladder, kidney, spleen, and gonadal), and then the causal network of internal organs and body weight of one-year-old P. ussuriensis was analyzed by path analysis, and sex-specific regression models were developed. The results showed that the correlations between body weight and the masses of the intestine, liver, swim bladder, kidney, and gonad were significant, while the spleen mass showed a significant positive correlation with body weight. Path analysis revealed that the direct path coefficients of the intestine, liver, swim bladder, kidney, and gonad on body weight were significant, and that of the spleen was significant. Through regression analysis, multiple linear regression equations were established. Importantly, the swim bladder had the greatest direct effect on body weight in males, whereas the intestine exhibited the strongest direct effect in females. These findings provide valuable insights for the selection and breeding of P. ussuriensis based on visceral indices.

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Pollen Sedimentary Dynamics and Hydroclimatic Implications in the Largest Lake System in Qaidam Basin, Northeastern Qinghai-Tibet Plateau - Hongyu Li; Haicheng Wei; Chenyu Wang; Aiying Cheng; Chunliang Gao; Hongpan Xue; Ronglei Duan; Shun Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Changes in the physiological indicators and gene expression for grass carp (Ctenopharyngodon idella) in response to alkaline stress - Qi Chen; Jianbo Zheng; Yi Xu; Fei Li; Shili Liu; Wenping Jiang; Meili Chi; Shun Cheng; Haiqi Zhang (Aquaculture International, 2025)

Synergistic acceleration of proton migration in osmotic microbial fuel cell: hydrophilic nanochannels coupling acid-base pairs created by functionalized metal-organic frameworks in forward osmosis membrane - Enling Tian; Yuan Liu; Cheng Song; Xingzu Wang; Fengjun Yin; Ling Fang; Shun Lu; Yu Lei; Hong Liu (Water Research, 2025)

Metalloporphyrin MOF-derived “quasi-carbon” materials featuring well-defined Co N4 sites as bifunctional electrocatalysts for enhanced zinc-air batteries performance - Yungang Sun; Kexin Xiong; Guoxin Zhang; Kairen Cheng; Shaoqing Feng; Huicong Chen; Meiyun Li; Kai Chen; Yihuang Chen; Huile Jin; Shun Wang (Chemical Engineering Journal, 2025)

Highly Efficient NO Conversion on Layered Photocatalysts: Surface Active Site Regulation and Molecule Activation - Yizhou Zhi; Yanfeng Lu; Yu Huang; Xianghan Li; Shun Cheng Lee (Aerosol Science and Engineering, 2025)

Cooperative nuclear import of duck plague virus DNA polymerase subunits: pUL42 NLS Enhances pUL30 nuclear import and viral replication, with VP22 as a compensatory factor - Yuxi Cui; Mingshu Wang; Anchun Cheng; Qiao Yang; Xumin Ou; Di Sun; Yu He; Xinxin Zhao; Ying Wu; Shaqiu Zhang; Bin Tian; Juan Huang; et al. (Veterinary Microbiology, 2025)

One-pot synthesis of visible-light responsive BiOCl/BiOBr/g-C3N4 ternary heterojunction with excellent photocatalytic activity - Lijun Cheng; Jianhua Shi; Bingjing Yao; Yiyun Peng; Wenhui Li; Shun Xin; Hua Gao; Shaohua Ma (Journal of Water Process Engineering, 2025)

Dynamic performance tests and multi-parametric refinement models of high-energy dissipation viscoelastic materials for seismic performance enhancement of engineering structures - Yao-Rong Dong; Zhao-Dong Xu; Lihua Zhu; Bao-Shun Wang; Yang Yang; Yu Cheng (Engineering Structures, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Evaluation of Seaweed Meal and Konjac Glucomannan Mixture as Feed Ingredients in Largemouth Bass Micropterus salmoides - Yan-Bo Cheng; Dan Wu; Liang Gao; Shun Rong; Guo-Huan Xu; Xu-Fang Liang (Fishes, 2025)
To address the negative effects of high-starch diets on largemouth bass (LMB), this study evaluated the feasibility of using a Gracilaria lemaneiformis-konjac glucomannan mixture (GKM, 2:1) as a substitute for strong flour (SF). Four iso-nitrogenous and iso-lipid diets were formulated: a control (15% SF; GK00) and three other diets replacing 33.3% (GK05), 66.7% (GK10), or 100% (GK15) of SF with GKM. Each diet was randomly administered to triplicate tanks of fish (10.49 ± 0.232 g) for a 10-week feeding trial. Results showed that the GKM inclusion groups significantly improved the fish survival and feed intake. Fish in GK05 and GK10 groups exhibited significantly higher final body weight, weight gain, and specific growth rate than the GK00 group, while GK15 showed no significant increase in these metrics. There was no impairment in protein, lipid, phosphorus, and energy retention efficiency in the GK05 and GK10 groups compared to those of the GK00 group. Apparent digestibility for feed dry matter, protein, lipid, phosphorus, and the 16 amino acids was not decreased in the GK05 and GK10 groups relative to the GK00 group. In addition, this study revealed reduced phosphorus waste per kilogram of weight gain in GK05 and GK10. In conclusion, these findings position GKM as a sustainable alternative to SF in feed for LMB.

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Exogenous application of artificial humic substance can improve black soil properties and rice yield - Yue YUAN; Qingyu LIU; Shun ZHANG; Zhuqing LIU; Xi ZHANG; Kui CHENG; Fan YANG (Pedosphere, 2025)

Heterotrophic nitrification-aerobic denitrification strains: An overlooked microbial interaction nexus in the anaerobic-swing-anoxic-oxic (ASAO) plug-flow system - Run-Ze Xu; Jia-Shun Cao; Song Cheng; Jing-Yang Luo; Bing-Jie Ni; Fang Fang; Weijing Liu; Peifang Wang (Journal of Environmental Management, 2025)

Impact of Coal-Fired Power Plants on Suspended Sediment Concentrations in Coastal Waters - Zhi-Cheng Huang; Po-Chien Lin; Po-Hsun Lin; Shun-Hsing Chuang (Journal of Marine Science and Engineering, 2025)
Many coastal coal-fired power plants utilize seawater flue gas desulfurization (SWFGD) systems, which may pose risks of heavy metal attachment on suspended sediments. Understanding variations in suspended sediment concentration (SSC) is therefore useful for controlling marine pollution. We studied two power plants as examples of discharging SSC using continuous measurement techniques. Monitoring sites at intake and discharge points and the surrounding coastal areas of the power plants was conducted across seasons. The first case study, Linkou Power Plant, is located in a high-SSC region influenced by monsoon winds and wave activity. Results indicate that SSC levels at all the monitoring sites are correlated with environmental factors of wind and wave conditions, with strong positive correlations observed between the intake and discharge points. In contrast, the Dalin Power Plant is located within an international harbor, where the SSC levels are generally low; however, sudden increases in SSC are observed at the intake point due to disturbances from vessel activities. These sudden increases are not evident at the discharge point, suggesting a sink of SSC may occur within the system. These results demonstrate that the two studied power plants have limited effects on the increase in SSC; the SSC in the discharge point is mainly related to the SSC input at the intake point. Effective management of SSC at the intake may help mitigate coastal pollution caused by SSC discharge and reduce the risk of harmful substances adhering to suspended solids in the discharging wastewater.

Corrigendum to “Cryopreservation of porcine skin-derived stem cells using melatonin or trehalose maintains their ability to self-renew and differentiate” [Cryobiology 107 (2022) 23–34] - Jia-Dong Sun; Yu Sun; Tian Qiao; Shu-Er Zhang; Paul W. Dyce; Yuan-Wei Geng; Ping Wang; Wei Ge; Wei Shen; Shun-Feng Cheng (Cryobiology, 2025)

LPA reduces the apoptosis of cryopreserved porcine skin-derived stem cells by inhibiting the regulatory factor TNF-α - Xin-Xiang Xie; Jia-Dong Sun; Ming-Xin Zang; Geng Zhang; Chun-Xiao Li; Xiang-Wei Zhai; Wei Shen; Wei Ge; Shun-Feng Cheng (Cryobiology, 2025)

Deformation Characteristics and Stability Analysis of Soft-Hard Interbedded Tunnels - Mei-li Hu; Shun-chuan Wu; Shi-jiang Pu; Hai-yong Cheng; Ji-quan Ma (Geotechnical and Geological Engineering, 2025)

Large-deformation analyses of seismic landslide runout considering spatially random soils and stochastic ground motions - Shun-Ping Ren; Yang Li; Xue-Jian Chen; Po Cheng; Fei Liu; Kai Yao (Bulletin of Engineering Geology and the Environment, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Anti-tembusu virus of capsid-targeted viral inactivation delivered by lentiviral vector in vivo - Xingcui Zhang; Ning Luo; Hui Ni; Anchun Cheng; Mingshu Wang; Shun Chen; Dekang Zhu; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Veterinary Microbiology, 2025)

Yield more in the shadow: Mitigating shading-induced yield penalty of maize via optimizing source-sink carbon partitioning - Xiao-Gui Liang; Hui-Min Chen; Yu-Qiang Pan; Zhi-Wei Wang; Cheng Huang; Zhen-Yuan Chen; Wang Tang; Xian-Min Chen; Si Shen; Shun-Li Zhou (European Journal of Agronomy, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

Evaluating long-term reductions in trace metal emissions from shipping in Shanghai - Meng Wang; Yusen Duan; Juntao Huo; Jia Chen; Yanfen Lin; Qingyan Fu; Tao Wang; Yu Huang; Junji Cao; Shun-cheng Lee (Journal of Hazardous Materials, 2024)

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Azotosporobacter soli gen. nov., sp. nov., a novel nitrogen-fixing bacterium isolated from paddy soil - Cheng-Jie Xie; Ling Yao; Rong Tang; Shuang Han; Shang Yang; Hend Alwathnani; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

Two novel Fe(III)-reducing bacteria, Geothrix campi sp. nov. and Geothrix mesophila sp. nov., isolated from paddy soils - Shuang Han; Shang Yang; Rong Tang; Cheng-Jie Xie; Xing Liu; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Duck plague virus-encoded microRNA dev-miR-D28-3p inhibits viral replication via targeting UL27 - Hui Ni; Xingcui Zhang; Juan Huang; Mingshu Wang; Anchun Cheng; Mafeng Liu; Dekang Zhu; Shun Chen; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Veterinary Microbiology, 2024)

Effective purification of phosphate from water using ultra-small hydrated cerium oxides encapsulated inside gel-type polymer - Shun Qiu; Zhanxun Chen; Jiao Li; Xinwei Zhang; Kaizhen Zhang; Pengfei Shen; Sikai Cheng; Chenghan Ji; Hui Qiu; Zhuoyao Fang; Xiaolin Zhang (Chemical Engineering Journal, 2024)

A sulfhydryl-functionalized vinylene-linked covalent organic framework for promoting gold recovery by light-assistance - Di Jiang; Zhen-Lei Wang; Yuan-Zhe Cheng; Ya-Xi Yu; Hui-Yuan Kong; Xin-Yue Bian; Xiao-Meng Dou; Shun-Li Li; Dong-Hui Yang; Xuesong Ding; Bao-Hang Han (Chemical Engineering Journal, 2024)

Corrigendum to “Detrimental effect of bisphenol S in mouse germ cell cyst breakdown and primordial follicle assembly” [Chemosphere. 2021 Feb;264(Pt 1):128445] - Wen-Xiang Liu; Farini Donatella; Shao-Jing Tan; Wei Ge; Jun-Jie Wang; Xiao-Feng Sun; Shun-Feng Cheng; Wei Shen (Chemosphere, 2024)

Study on seismic response of liquefiable soil-pile group considering pile cap and soil contact - Zhang Xiao-ling; Lan Hao; Xu Cheng-shun; Han Yan (Soil Dynamics and Earthquake Engineering, 2024)

The calculation method of vertical bearing capacity of pile foundation considering cyclic weakening effect of soft clay - Zhang Xiao-ling; Zhang Xiao-wei; Xu Cheng-shun; Wu Yang (Computers and Geotechnics, 2024)

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Effective oxidation and adsorption of As(III) in water by nanoconfined Ce-Mn binary oxides with excellent reusability - Shun Qiu; Zhanxun Chen; Ling Yu; Chuying Liu; Chenghan Ji; Pengfei Shen; Sikai Cheng; Hui Qiu; Zhuoyao Fang; Xiaolin Zhang (Journal of Hazardous Materials, 2024)

Crenobacter oryzisoli sp. nov., a novel phosphate-solubilizing bacterium isolated from the paddy soil - Shu-Qun Zhang; Cheng-Jie Xie; Ling Yao; Christopher Rensing; Hao Lin; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2024)

Applicability of Variable-Geometry Turbocharger for Diesel Generators under High Exhaust Back Pressure - Chien-Cheng Chen; Yuan-Liang Jeng; Shun-Chang Yen (Journal of Marine Science and Engineering, 2024)
The exhaust back pressure of diesel engines is becoming increasingly higher nowadays. In order to keep discharging exhaust unhindered and operating smoothly under high exhaust back pressure, a large reduction in engine maximum brake output is often observed, as well as increased fuel consumption and lower combustion efficiency with heavy exhaust smokes. In our previous study, “Applicability of Reducing Valve Timing Overlap for Diesel Engines under High Exhaust Back Pressure”, a reduced valve timing overlap of 12 °CA partially improves the brake output and BSFC for a fixed-geometry turbocharged diesel engine under high exhaust back pressures. A potential solution for restoring the brake output under high exhaust back pressures could be the use of variable-geometry turbochargers. In this study, a variable-geometry turbocharger is applied to a diesel engine to study the engine performance characteristics and applicability, especially the further improvement of brake output and the brake-specific fuel consumption of the engine. Continuing with the results of our previous research, a basic setting of 12 °CA for the valve timing overlap is set up for the subsequent engine performance simulations in this study (using GT-Power SW). Via simulation, exhaust back pressures of 25 kPa, 45 kPa, and 65 kPa gauge are studied for a turbocharged diesel engine. The results for the engine parameters, including brake output, brake-specific fuel consumption, compressor outlet temperature, turbine inlet temperature, intake air mass flow rate, and exhaust mass flow rate are analyzed. The results of the variable-geometry turbocharger, including turbocharger speed, pressure ratios and efficiencies of compressor and turbine are also analyzed. The results indicate that the brake output and brake-specific fuel consumption are effectively improved under full-load operation with an adequate variable-geometry turbocharger rack position. Operable ranges of rack position are also set up for different back pressures.

Fatigue damage analysis method of offshore wind turbine foundation - Xiao-Ling Zhang; Bing-jie Zhang; Dong Wang; Cheng-shun Xu (Ocean Engineering, 2024)

Early warning for thermal runaway in lithium-ion batteries during various charging rates: Insights from expansion force analysis - Kuijie Li; Long Chen; Xuebing Han; Xinlei Gao; Yao Lu; Depeng Wang; Shun Tang; Weixin Zhang; Weixiong Wu; Yuan-cheng Cao; Languang Lu; Jinyu Wen; et al. (Journal of Cleaner Production, 2024)

Enhancing proton conduction by regulating proton carrier position in polyamide layer of forward osmosis membrane in osmotic microbial fuel cell - Enling Tian; Yuan Liu; Xingzu Wang; Ling Fang; Lei Zheng; Cheng Song; Shun Lu; Hong Liu (Chemical Engineering Journal, 2024)

Quantifying denudation rates and sediment recycling of low-relief, high-elevation landscapes using in-situ and meteoric cosmogenic nuclides - Ye Yang; Shun-Cheng Zhang; Jia-Xin Zhang; Li-Feng Cui; Cong-Qiang Liu; Sheng Xu (Geochimica et Cosmochimica Acta, 2024)

Cross-talk between Vimentin and autophagy regulates blood-testis barrier disruption induced by cadmium - Na Chen; Xiaoyan Wan; Mei Wang; Yamin Li; Xiaofei Wang; Ling Zeng; Jinzhao Zhou; Yanwei Zhang; Shun Cheng; Yi Shen (Environmental Pollution, 2024)

Extracellular Vesicles Derived from Glioma Stem Cells Affect Glycometabolic Reprogramming of Glioma Cells Through the miR-10b-5p/PTEN/PI3K/Akt Pathway - Shun Li; Lifang Mao; Lvmeng Song; Xiaochao Xia; Zihao Wang; Yinchuan Cheng; Jinqing Lai; Xiaoping Tang; Xiangrong Chen (Stem Cell Reviews and Reports, 2024)

Exogenous modification of EL-4 T cell extracellular vesicles with miR-155 induce macrophage into M1-type polarization - Bikash R. Giri; Shun Li; Guofeng Cheng (Drug Delivery and Translational Research, 2024)

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Effects of feeding and reverse feeding jellyfish on the growth of Pampus argenteus juveniles and the detoxification of jellyfish toxins by serine protease - Shun Zhang; Chunyang Guo; Xiaofang Zhu; Cheng Zhang; Kai Liao; Shanliang Xu; Danli Wang (Aquaculture, 2024)

Persistent free radicals on biochar for its catalytic capability: A review - Xiaoqing Liu; Zhijie Chen; Shun Lu; Xingdong Shi; Fulin Qu; Dongle Cheng; Wei Wei; Ho Kyong Shon; Bing-Jie Ni (Water Research, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

A continuous digital elevation representation model for DEM super-resolution - Shun Yao; Yongmei Cheng; Fei Yang; Mikhail G. Mozerov (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

TET1 Regulates Proliferation of Mouse Skin-Derived Stem Cells In Vitro - Tian Qiao; Li Li; Ming-Xin Zang; Yi-Nuo Jiang; Sha-Sha Wang; Chun-Xiao Li; Xin-Xiang Xie; Geng Zhang; Ying Zhang; Wei Ge; Wei Shen; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

Study on different reinforcement methods of inclined liquefiable site - Xiao-ling Zhang; Hao Lan; Xian-hui Zhao; Cheng-shun Xu; Ke-min Jia (Soil Dynamics and Earthquake Engineering, 2024)

Emergence and mobilization of a novel lincosamide resistance gene lnu(I): From environmental reservoirs to pathogenic bacteria - Zhishuang Yang; Tianjing Lan; Hongyan Luo; Pei Li; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Science of The Total Environment, 2024)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Probabilistic fatigue analysis on a central holed thick steel plate of C1 Wedge Connection for wind turbine tower assembling - Ding Liao; Lu Cheng; José Correia; Milan Veljkovic; Shun-Peng Zhu; Jasper Winkes; Koen Creusen; Filippo Berto (Ocean Engineering, 2023)

Transcriptome analysis of turbot (Scophthalmus maximus) kidney responses to inactivated bivalent vaccine against Aeromonas salmonicida and Edwardsiella tarda - Yunji Xiu; Baoshan Guo; Zongrui Yang; Jingyuan Yi; Huimin Guo; Hetron Mweemba Munang'andu; Cheng Xu; Shun Zhou (Fish & Shellfish Immunology, 2023)

Scale-dependent responses of ecosystem service trade-offs to urbanization in Erhai Lake Basin, China - Huangxi Qin; Shun Li; Jiwen Sun; Jianghao Cheng (Environmental Science and Pollution Research, 2023)

NS5 hijacks TRAF3 to inhibit type I interferon signaling during duck Tembusu virus infection - Wenjun Cai; Yuhong Pan; Wanshuang Luo; Anchun Cheng; Mingshu Wang; Shun Chen; Juan Huang; Qiao Yang; Ying Wu; Di Sun; Sai Mao; Dekang Zhu; et al. (Veterinary Microbiology, 2023)

Heterogeneous photocatalytic conversion of biomass to biofuels: A review - Xiaoqing Liu; Zhijie Chen; Shun Lu; Bentuo Xu; Dongle Cheng; Wei Wei; Yansong Shen; Bing-Jie Ni (Chemical Engineering Journal, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Exposure and health risk assessment of PM2.5-bound polycyclic aromatic hydrocarbons during winter at residential homes: A case study in four Chinese cities - Zhuozhi Zhang; Qi Yuan; Meng Wang; Tafeng Hu; Yu Huang; Guangli Xiu; Senchao Lai; Yuan Gao; Shun Cheng Lee (Science of The Total Environment, 2023)

Molecular Cloning and Expression Analysis of Lipoprotein Lipase (LPL) From Pampus Argenteus - Shun Zhang; Mengdi Liu; Xiaojing Zhu; Chuangyuan Lin; Cheng Zhang; Xuemei Yan; Danli Wang; Shanliang Xu (Thalassas: An International Journal of Marine Sciences, 2023)

Neem oil against Aeromonas hydrophila infection by disrupting quorum sensing and biofilm formation - Shengping Li; Qiuhong Yang; Bo Cheng; Yongtao Liu; Shun Zhou; Xiaohui Ai; Jing Dong (Biofouling, 2023)

Infection dynamic of Micropterus salmoides rhabdovirus and response analysis of largemouth bass after immersion infection - Shunfa Yi; Youjun Wu; Xie Gu; Yan Cheng; Zesheng Zhang; Zhenzhen Yuan; Hongbao Xie; Shichao Qian; Mengmeng Huang; Hui Fei; Shun Yang (Fish & Shellfish Immunology, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Effects of different test methods on the seismic dynamic response in inclined liquefiable soil - Xiao-ling Zhang; Xian-hui Zhao; Cheng-shun Xu; Ke-min Jia; Yan Han (Soil Dynamics and Earthquake Engineering, 2023)

Selective flotation separation of hemimorphite from quartz using the biosurfactant sodium N-lauroylsarcosinate as a novel collector - Kai Jia; Yuhang Lu; Jiang Liu; Shun Cheng; Shiqiang Liu; Yijun Cao; Guosheng Li (Minerals Engineering, 2023)

Large-deformation modelling of earthquake-triggered landslides considering non-uniform soils with a stratigraphic dip - Shun-Ping Ren; Xue-Jian Chen; Zeng-Le Ren; Po Cheng; Yong Liu (Computers and Geotechnics, 2023)

Solvent-free quasi-solid polymer electrolyte with a high dielectric constant for stable lithium metal anodes - Xuechun Lou; Jun Zhong; Danpeng Cheng; Qigao Han; Fuhe Wang; Shuaijing Ji; Wuxin Sha; Fengqian Wang; Jie Tian; Weixin Zhang; Shun Tang; Yuan-Cheng Cao; et al. (Chemical Engineering Journal, 2023)

Influence analysis of overlying soil layer to seismic behavior of inclined liquefiable soil and pile interaction system - Xiao-ling Zhang; Li-jing Fang; Cheng-shun Xu; Ke-min Jia; Yan Han (Soil Dynamics and Earthquake Engineering, 2023)

Effects of forest management practices on carbon dynamics of China's boreal forests under changing climates - Chao Huang; Shun Li; Hong S. He; Yu Liang; Wenru Xu; Mia M. Wu; Zhiwei Wu; Cheng Huang; Fusheng Chen (Journal of Environmental Management, 2023)

Sulfurospirillum oryzae sp. nov., A Novel Nitrogen-Fixing Bacterium Isolated from Paddy Soil - Cheng-Jie Xie; Shang Yang; Rong Tang; Shuang Han; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Deleting UL49.5 in duck plague virus causes attachment, entry and spread defects - Chunmei Li; Mingshu Wang; Anchun Cheng; Bin Tian; Juan Huang; Ying Wu; Qiao Yang; Qun Gao; Di Sun; Shaqiu Zhang; Xumin Ou; Sai Mao; et al. (Veterinary Microbiology, 2023)

Long-term variation and evaluation of air quality across Hong Kong - Yan Tan; Shuwen Han; Yi Chen; Zhongbiao Wu; Shun-cheng Lee (Journal of Environmental Sciences, 2023)

Geothrix oryzisoli sp. nov., a ferric iron-reducing bacterium isolated from paddy soil - Shuang Han; Rong Tang; Shang Yang; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Duck plague virus pUL15 performs a nonspecial cleavage activity through its C terminal nuclease domain in vitro - Qiao Yang; Yiheng Liu; Mingshu Wang; Ying Wu; Tian Bin; Xumin Ou; Sai Mao; Juan Huang; Di Sun; Qun Gao; Xinxin Zhao; Shaqiu Zhang; et al. (Veterinary Microbiology, 2023)

Duck IL-7 as a novel adjuvant improves the humoral immune response to an inactivated duck tembusu virus vaccine - Juan Huang; Tingting Yu; Zhiyao Long; Mingshu Wang; Mafeng Liu; Dekang Zhu; Shun Chen; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; Xumin Ou; et al. (Veterinary Microbiology, 2023)

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Shouchella tritolerans sp. nov., a facultative anaerobic bacterium isolated from marine sediments - Cheng-Jie Xie; Shang Yang; Shuang Han; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2023)

As3MT is related to relative RNAs and base modifications of p53 in workers exposed to arsenic - Weihua Wen; Shun Zha; Huirong Cheng; Jun Qi; Qian Chen; Yun Gu (Environmental Science and Pollution Research, 2023)

Effects of acute resistance exercise with different loads on appetite, appetite hormones and autonomic nervous system responses in healthy young men - Hung-Wen Liu; Hao-Chien Cheng; Shun-Hsi Tsai; Yi-Te Shao (Appetite, 2023)

Volatile organic compounds at a roadside site in Hong Kong: Characteristics, chemical reactivity, and health risk assessment - Shuwen Han; Yan Tan; Yuan Gao; Xinwei Li; Steven Sai Hang Ho; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

A novel sulfate-reducing and nitrogen-fixing bacterium Fundidesulfovibrio soli sp. nov., isolated from paddy soils - Shang Yang; Rong Tang; Cheng-Jie Xie; Shuang Han; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2023)

Open water characteristics of marine propeller with superhydrophobic surfaces - Lie Chen; Shun Wang; Jiangming Ding; Yutao Wang; Peter Bennett; Jian Cheng; Qibiao Yang; Dun Liu (Ocean Engineering, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

The characteristics of stepwise ultrasonic hydrolysates of sludge for enhancing denitrification - Bo-Cheng You; Cheng-Chung Huang; Shun-Hsing Chuang (Bioresource Technology, 2023)

Bacillus litorisediminis sp. nov., a Thermophilic Bacterium Isolated from Mangrove Sediment - Rong Tang; Shang Yang; Shuang Han; Cheng-Jie Xie; Guan-Min Huang; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

Fundidesulfovibrio agrisoli sp. nov., A Nitrogen-Fixing Bacterium Isolated from Rice Field - Shang Yang; Rong Tang; Shuang Han; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Current Microbiology, 2023)

A novel nitrogen-fixing bacterium, Propionivibrio soli sp. nov. isolated from paddy soil - Cheng-Jie Xie; Rong Tang; Shang Yang; Shuang Han; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Development of new technology for tar removal in IGCC - Yi-Shun Chen; Shu-San Hsiau; Cheng-En Liao; Shih-Hao Chou (Journal of Cleaner Production, 2023)

The role of TNF-α in the phagocytosis of largemouth bass (Micropterus salmoides) leukocytes - Shun Yang; Yuanxin Ma; Xiaocong Lou; Zhewei Zhou; Huimin Zhang; Shunfa Yi; Yan Cheng; Shichao Qian; Mengmeng Huang; Hui Fei (Fish & Shellfish Immunology, 2023)

Changes in the gene expression and gut microbiome to the infection of decapod iridescent virus 1 in Cherax quadricarinatus - Jianbo Zheng; Yongyi Jia; Fei Li; Meili Chi; Shun Cheng; Shili Liu; Wenping Jiang; Yinuo Liu (Fish & Shellfish Immunology, 2023)

Isoporous catalytic ceramic membranes for ultrafast contaminants elimination through boosting confined radicals - Xinsheng Luo; Shun Yu; Daliang Xu; Junwen Ding; Xuewu Zhu; Jiajian Xing; Teng Wu; Xiang Zheng; Tejraj M. Aminabhavi; Xiaoxiang Cheng; Heng Liang (Chemical Engineering Journal, 2023)

Correction to: Description of two nitrogen‑fixing bacteria, Geomonas fuzhouensis sp. nov. and Geomonas agri sp. nov., isolated from paddy soils - Shang Yang; Guo-Hong Liu; Rong Tang; Shuang Han; Cheng-Jie Xie; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2023)

Oxygen vacancy engineering of photocatalytic nanomaterials for enrichment, activation, and efficient removal of nitrogen oxides with high selectivity: a review - Yanfeng Lu; Meijuan Chen; Liu Jiang; Jun-ji Cao; Haiwei Li; Shun Cheng Lee; Yu Huang (Environmental Chemistry Letters, 2022)

Two ferric-reducing bacteria Geothrix terrae sp. nov. and Geothrix alkalitolerans sp. nov., isolated from paddy soil - Shuang Han; Rong Tang; Shang Yang; Cheng-Jie Xie; Manik Prabhu Narsing Rao; Guo-Hong Liu; Shun-Gui Zhou (Archives of Microbiology, 2022)

Analyses of growth performance and realized heritability of Pampus argenteus in a breeding program in China - Cheng Zhang; Kimran Jean Jacques; Shun Zhang; Shanliang Xu; Yajun Wang; Danli Wang (Frontiers in Marine Science, 2022)
Silver pomfret ( Pampus argenteus ) is an economically important mariculture species. However, little is known about the genetic parameters of its commercially important traits. In order to determine whether continuous progress can be achieved by selection for growth, we took the body weight trait of East China Sea P. argenteus as the target trait of mass selection. The realized heritability of P. argenteus from the selected group and control group was analyzed at the three growth times (60, 90, and 120 days). The results showed that the growth performance parameters of the selected group in the third month post hatching were higher than those in the control group, but the opposite results were found in the fourth month. The morphological traits highly correlated with the body weight of P. argenteus were found by Pearson correlation analysis and path analysis, which were body length and tail length, respectively. On the 60th, 90th, and 120th days after hatching, the genetic gains of body weight trait in the selected group were 9.44%, 17.64%, and 15.18%, respectively, and the mean values of realized heritability were at moderate level. Nevertheless, in the selected group, the genetic variation values of the two morphological traits significantly related to body weight were all below 10%, and the genetic gains were relatively low and stable, but the genetic variation values of body weight trait in the selected group were above 20%, and genetic gains were relatively high. These implied that it is possible to obtain considerable genetic gains by selecting for body weight trait, and the results provide supportive evidence for the continuity of the P. argenteus -selective breeding program.

Trochanteric Nails for the Reduction of Intertrochanteric Fractures: A Biomechanical Analysis Based on Finite Element Analysis and DIC System - Ming-Tzu Tsai; Cheng-Hung Lee; Kun-Hui Chen; Yu-Chun Yen; Chun-Hsiang Wang; Shun-Ping Wang; Kuo-Chih Su (Journal of Medical and Biological Engineering, 2022)
Purpose Intertrochanteric fractures are common among femoral fractures in the elderly population. The trochanteric nail is a standard internal fixator used in treating femoral intertrochanteric fractures. The technique of femoral fracture reduction affects the postoperative outcome. Here, we applied finite element analysis (FEA) to study mechanical effects of different reduction approaches using the trochanteric nail in treating both stable and unstable intertrochanteric fractures. Methods We combined FEA and in vitro experiments using a digital imaging correlation (DIC) technique to study effects of different alignment conditions after treating 4 cases of intertrochanteric fractures using the trochanteric nail system. A downward force of 2250 N was applied to the femoral head, and the distal end of the femur was fixed. The observed indicators were the femur displacement, together with the stress on the femur and trochanteric nail system. In addition, the displacement distribution was analyzed using DIC. Results In the case of space reduction, the force was transmitted by the trochanteric nail system, resulting in greater stress imposed on the femur or the trochanteric nail system. In the case of closed reduction, the stress was much smaller. In the case of unstable fracture reduction, closed reduction was associated with a smaller contact area at the fracture site, resulting in greater stress on both trochanter and the trochanteric nail system. Conclusion When the trochanteric nail system was used for fixation, the fracture site was well aligned, reducing the stress on the femur or the trochanteric nail.

Should Plate-Bone Gap be Preserved in Far-Cortical Locking Technique? A Biomechanical Study - Shun-Ping Wang; Yang-Chen Chou; Cheng-En Hsu; Chi-Wen Chou; Chao-Ping Chen; Kun-Jhih Lin; Fuu-Cheng Jiang; Wen-Chuan Chen; Chen-Chiang Lin (Journal of Medical and Biological Engineering, 2022)

Relationships of multiple metals exposure, global DNA methylation, and urothelial carcinoma in central Taiwan - Hui-Tsung Hsu; Hui-Ling Lee; Hsu-Hui Cheng; Chao-Hsiang Chang; Chiu-Shong Liu; Po-Jen Hsiao; Han Chang; Chi-Shun Lien; Mu-Chi Chung; Chi-Jung Chung (Archives of Toxicology, 2022)

Neural responses to facial attractiveness in the judgments of moral goodness and moral beauty - Qiuping Cheng; Zhili Han; Shun Liu; Yilong Kong; Xuchu Weng; Lei Mo (Brain Structure and Function, 2022)

CAV1 is a prognostic predictor for patients with idiopathic pulmonary fibrosis and lung cancer - Dongdong Yin; Jiayang Qiu; Suxia Hu; Longqiang Cheng; Hui Li; Xingpu Cheng; Shun Wang; Jun Lu (Journal of Biosciences, 2022)

Description of two nitrogen-fixing bacteria, Geomonas fuzhouensis sp. nov. and Geomonas agri sp. nov., isolated from paddy soils - Shang Yang; Guo-Hong Liu; Rong Tang; Shuang Han; Cheng-Jie Xie; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2022)

YAP regulates porcine skin-derived stem cells self-renewal partly by repressing Wnt/β-catenin signaling pathway - Hong-Chen Yan; Yu Sun; Ming-Yu Zhang; Shu-Er Zhang; Jia-Dong Sun; Paul W. Dyce; Francesca Gioia Klinger; Massimo De Felici; Wei Shen; Shun-Feng Cheng (Histochemistry and Cell Biology, 2022)

Comparison of Primary Production Using in situ and Satellite-Derived Values at the SEATS Station in the South China Sea - Yung-Yen Shih; Fuh-Kwo Shiah; Chao-Chen Lai; Wen-Chen Chou; Jen-Hua Tai; Yu-Shun Wu; Cheng-Yang Lai; Chia-Ying Ko; Chin-Chang Hung (Frontiers in Marine Science, 2021)
Satellite-based observations of primary production (PP) are broadly used to assess carbon fixation rate of phytoplankton in the global ocean with small spatiotemporal limitations. However, the remote sensing can only reach the ocean surface, the assumption of a PP vertically exponential decrease with increasing depth from the surface to the bottom of euphotic zone may cause a substantial and potential discrepancy between in situ measurements and satellite-based observations of PP. This study compared euphotic zone integrated PP derived from measurements based on ship-based in situ incubation (i.e., PP in situ ) and those derived from the satellite-based vertically generalized production model (VGPM; PP VGPM ) for the period 2003∼2016 at the South East Asian Time-series Study (SEATS) station. PP values obtained during the NE-monsoon (NEM: Nov∼Mar; PP in situ = 323 ± 134; PP VGPM = 443 ± 142 mg-C m –2 d –1 ) were ∼2-fold higher than those recorded during the SW-monsoon (SWM: Apr∼Oct; PP in situ = 159 ± 58; PP VGPM = 250 ± 36 mg-C m –2 d –1 ), regardless of the method used for derivation. The main reason for the higher PP values during the NEM appears to have been a greater abundance of inorganic nutrients were made available by vertical advection. Note that on average, PP in situ estimates were ∼50% lower than PP VGPM estimates, regardless of the monsoon. These discrepancies can be mainly attributed to differences from the euphotic zone depth between satellite-based and in situ measurements. The significantly negative relationship between PP measurements obtained in situ and sea surface temperatures observed throughout this study demonstrates that both methods are effective indicators in estimating PP. Overall, our PP in situ analysis indicates that a warming climate is unfavorable for primary production in low-latitude open ocean ecosystems.

Relationship between expression of matrix metalloproteinase-9 and feeding on jellyfish in Pampus argenteus - Xuanyu Zhou; Shun Zhang; Xiaofang Zhu; Chunpu Zhao; Shun Cheng; Shanliang Xu; Danli Wang (Aquaculture International, 2021)

Identification and functional characterization of a PDR transporter in Tripterygium wilfordii Hook.f. that mediates the efflux of triptolide - Guopeng Miao; Juan Han; Yan-bo Huo; Cheng-run Wang; Shun-chang Wang (Plant Molecular Biology, 2021)

Population-based meta-analysis of chloroquine: informing chloroquine pharmacokinetics in COVID-19 patients - Xueting Yao; Xiaoyu Yan; Xiaohan Wang; Ting Cai; Shun Zhang; Cheng Cui; Xiaoxu Wang; Zhe Hou; Qi Liu; Haiyan Li; Jing Lin; Zi Xiong; et al. (European Journal of Clinical Pharmacology, 2021)
Aims Chloroquine (CQ) has been repurposed to treat coronavirus disease 2019 (COVID-19). Understanding the pharmacokinetics (PK) in COVID-19 patients is essential to study its exposure–efficacy/safety relationship and provide a basis for a possible dosing regimen optimization. Subject and methods In this study, we used a population-based meta-analysis approach to develop a population PK model to characterize the CQ PK in COVID-19 patients. An open-label, single-center study (ethical review approval number: PJ-NBEY-KY-2020-063-01) was conducted to assess the safety, efficacy, and pharmacokinetics of CQ in patients with COVID-19. The sparse PK data from 50 COVID-19 patients, receiving 500 mg CQ phosphate twice daily for 7 days, were combined with additional CQ PK data from 18 publications. Results A two-compartment model with first-order oral absorption and first-order elimination and an absorption lag best described the data. Absorption rate (ka) was estimated to be 0.559 h −1 , and a lag time of absorption (ALAG) was estimated to be 0.149 h. Apparent clearance (CL/F) and apparent central volume of distribution (V2/F) was 33.3 l/h and 3630 l. Apparent distribution clearance (Q/F) and volume of distribution of peripheral compartment (Q3/F) were 58.7 l/h and 5120 l. The simulated CQ concentration under five dosing regimens of CQ phosphate were within the safety margin (400 ng/ml). Conclusion Model-based simulation using PK parameters from the COVID-19 patients shows that the concentrations under the currently recommended dosing regimen are below the safety margin for side-effects, which suggests that these dosing regimens are generally safe. The derived population PK model should allow for the assessment of pharmacokinetics–pharmacodynamics (PK-PD) relationships for CQ when given alone or in combination with other agents to treat COVID-19.

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Identification of reproduction-related genes and pathways in the Culter alburnus H-P-G axis and characterization of their expression differences in malformed and normal gynogenetic ovaries - Yong Y. Jia; Mei L. Chi; Wen P. Jiang; Shi L. Liu; Shun Cheng; Jian B. Zheng; Zhi M. Gu (Fish Physiology and Biochemistry, 2021)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Pan-genome analysis of Riemerella anatipestifer reveals its genomic diversity and acquired antibiotic resistance associated with genomic islands - Dekang Zhu; Zhishuang Yang; Jinge Xu; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; Yunya Liu; et al. (Functional & Integrative Genomics, 2020)

Diverse Community Structures in the Neuronal-Level Connectome of the Drosophila Brain - Chi-Tin Shih; Yen-Jen Lin; Cheng-Te Wang; Ting-Yuan Wang; Chih-Chen Chen; Ta-Shun Su; Chung-Chuang Lo; Ann-Shyn Chiang (Neuroinformatics, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Investigation of factors affecting the gaseous and particulate matter emissions from diesel vehicles - Bei Wang; Yik-Sze Lau; Yuhan Huang; Bruce Organ; Shun-Cheng Lee; Kin-Fai Ho (Air Quality, Atmosphere & Health, 2019)

Molecular characterization and expression analysis of cyp19a gene in Culter alburnus - Jianbo Zheng; Yongyi Jia; Fei Li; Shili Liu; Meili Chi; Shun Cheng; Zhimi Gu (Fisheries Science, 2019)

Comparative genome‐scale modelling of the pathogenic Flavobacteriaceae species Riemerella anatipestifer in China - Jibin Liu; Qiurui Zeng; Mingshu Wang; Anchun Cheng; Mafeng Liu; Dekang Zhu; Shun Chen; Renyong Jia; Xin‐Xin Zhao; Ying Wu; Qiao Yang; Shaqiu Zhang; et al. (Environmental Microbiology, 2019)
Riemerella anatipestifer (RA) is a gram‐negative bacterium that has a high potential to infect waterfowl. Although more and more genomes of RA have been generated comparaed to genomic analysis of RA still remains at the level of individual species. In this study, we analysed the pan‐genome of 27 RA virulent isolates to reveal the intraspecies genomic diversity from various aspects. The multi‐locus sequence typing (MLST) analysis suggests that the geographic origin of R. anatipestifer is Guangdong province, China. Results of pan‐genome analysis revealed an open pan‐genome for all 27 species with the sizes of 2967 genes. We identified 387 genes among 555 unique genes originated by horizontal gene transfer. Further studies showed 204 strain‐specific HGT genes were predicted as virulent proteins. Screening the 1113 core genes in RA through subtractive genomic approach, 70 putative vaccine targets out of 125 non‐cytoplasmic proteins have been predicted. Further analysis of these non A. platyrhynchos homologous proteins predicted that 56 essential proteins as drug target with more interaction partners were involved in unique metabolic pathways of RA. In conclusion, the present study indicated the essence and the diversity of RA and also provides useful information for identification of vaccine and drugs candidates in future.

Antagonism of Ca2+-sensing receptors by NPS 2143 is transiently masked by p38 activation in mouse brain bEND.3 endothelial cells - Cing-Yu Chen; Mann-Jen Hour; Wen-Chuan Lin; Kar-Lok Wong; Lian-Ru Shiao; Ka-Shun Cheng; Paul Chan; Yuk-Man Leung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Enhancing tetrandrine cytotoxicity in human lung carcinoma A549 cells by suppressing mitochondrial ATP production - Louis W. C. Chow; Ka-Shun Cheng; Fai Leong; Chi-Wai Cheung; Lian-Ru Shiao; Yuk-Man Leung; Kar-Lok Wong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Seasonal behavior of water-soluble organic nitrogen in fine particulate matter (PM2.5) at urban coastal environments in Hong Kong - Steven Sai Hang Ho; Lijuan Li; Linli Qu; Junji Cao; Ka Hei Lui; Xinyi Niu; Shun-Cheng Lee; Kin Fai Ho (Air Quality, Atmosphere & Health, 2019)

Molecular identification of dmrt1 and its promoter CpG methylation in correlation with gene expression during gonad development in Culter alburnus - Yongyi Jia; Jianbo Zheng; Meili Chi; Shili Liu; Wenping Jiang; Shun Cheng; Zhimi Gu; Liqiao Chen (Fish Physiology and Biochemistry, 2019)

HDAC9 Polymorphisms Predict Susceptibility, Severity, and Short-Term Outcome of Large Artery Atherosclerotic Stroke in Chinese Population - Mengmeng Wang; Mengmeng Gu; Zibao Li; Bo Sun; Xi Cheng; Zhengze Dai; Shun Li; Lulu Xiao; Min Zhao; Zhaojun Wang; Ying Lin; Yahong Liu; et al. (Journal of Molecular Neuroscience, 2019)

Protection of melon against Fusarium wilt-root knot nematode complex by endophytic fungi Penicillium brefeldianum HS-1 - Guo-peng Miao; Juan Han; Ke-gui Zhang; Shun-chang Wang; Cheng-run Wang (Symbiosis, 2019)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Calpain inhibition attenuates bleomycin-induced pulmonary fibrosis via switching the development of epithelial-mesenchymal transition - Yuan Liu; Bing Liu; Gu-qin Zhang; Jing-feng Zou; Meng-lin Zou; Zhen-shun Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Low-dose diethylhexyl phthalate exposure does not impair the expressive patterns of epigenetics-related genes and DNA methylation of breast cancer-related genes in mouse mammary glands - Shun-Feng Cheng; Ling Li; Bo Li; Jing-Cai Liu; Fang-Nong Lai; Yong Zhao; Xi-Feng Zhang; Wei Shen; Lan Li (Molecular & Cellular Toxicology, 2018)

The complete mitochondrial genome sequence of Changbai Mountains wild boar (Cetartiodactyla: Suidae) - Zhen-Dong Tan; Lin-Yuan Shen; Xiao Cheng; Mai-Lin Gan; Shun-Hua Zhang; Li Zhu (Conservation Genetics Resources, 2018)

Nest-dismantling behavior of yellow-bellied prinia in mainland and island populations - Longwu Wang; Shun-Jen Cheng; Yu-Cheng Hsu; Wei Liang (acta ethologica, 2018)

The 3D protein of duck hepatitis A virus type 1 binds to a viral genomic 3′ UTR and shows RNA-dependent RNA polymerase activity - Yu Zhang; Qianda Cao; Mingshu Wang; Renyong Jia; Shun Chen; Dekang Zhu; Mafeng Liu; Kunfeng Sun; Qiao Yang; Ying Wu; Xinxin Zhao; Xiaoyue Chen; et al. (Virus Genes, 2017)

The aflatoxin-detoxifizyme specific expression in the parotid gland of transgenic pigs - An-gang Lou; Jin-shun Cai; Xue-mei Zhang; Cheng-dou Cui; Ying-shu Piao; Li-zeng Guan (Transgenic Research, 2017)

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Application of sodium alginate in induced biological soil crusts: enhancing the sand stabilization in the early stage - Chengrong Peng; Jiaoli Zheng; Shun Huang; Shuangshuang Li; Dunhai Li; Mingyu Cheng; Yongding Liu (Journal of Applied Phycology, 2017)

Three-Dimensional Bi $$_{5}$$ 5 O $$_{7}$$ 7 I Photocatalysts for Efficient Removal of NO in Air Under Visible Light - Wei Wang; Yu Huang; Xiaochao Zhang; Jun-ji Cao; Wingkei Ho; Shun Cheng Lee (Aerosol Science and Engineering, 2017)

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Applying the strategy of light environment control to improve the biomass and polysaccharide production of Nostoc flagelliforme - Pei-pei Han; Shi-gang Shen; Hui-Yan Wang; Shun-yu Yao; Zhi-lei Tan; Cheng Zhong; Shi-ru Jia (Journal of Applied Phycology, 2017)

The Pivotal Role of Ca2+ Homeostasis in PBDE-47-Induced Neuronal Apoptosis - Shun Zhang; Yihu Chen; Xue Wu; Hui Gao; Rulin Ma; Chunyang Jiang; Gang kuang; Guodong Zhao; Tao Xia; Xiaofei Zhang; Rongrong Lei; Cheng Zhang; et al. (Molecular Neurobiology, 2016)

Postnatal Stress Induced by Injection with Valproate Leads to Developing Emotional Disorders Along with Molecular and Cellular Changes in the Hippocampus and Amygdala - Chih-Yen Wang; Chien-Wen Cheng; Wei-Hua Wang; Po-See Chen; Shun-Fen Tzeng (Molecular Neurobiology, 2016)

The 2A2 protein of Duck hepatitis A virus type 1 induces apoptosis in primary cell culture - Jingyu Cao; Xumin Ou; Dekang Zhu; Guangpeng Ma; Anchun Cheng; Mingshu Wang; Shun Chen; Renyong Jia; Mafeng Liu; Kunfeng Sun; Qiao Yang; Ying Wu; et al. (Virus Genes, 2016)

Influence of ginseng cultivation under larch plantations on plant diversity and soil properties in Liaoning Province, Northeast China - Wei-wei Liu; Mou-cheng Liu; Wen-hua Li; Fan-shun Zeng; Yi Qu (Journal of Mountain Science, 2016)

Wheat yellow mosaic virus resistance in wheat cultivar Madsen acts in roots but not in leaves - Cheng Liu; Takako Suzuki; Kohei Mishina; Antje Habekuss; Angelika Ziegler; Chao Li; Shun Sakuma; Guoxiong Chen; Mohammad Pourkheirandish; Takao Komatsuda (Journal of General Plant Pathology, 2016)

The Detection of Hemin-Binding Proteins in Riemerella anatipestifer CH-1 - Hebin Liao; Mafeng Liu; Xingjun Cheng; Dekang Zhu; Mingshu Wang; Renyong Jia; Shun Chen; Kunfeng Sun; Qiao Yang; Francis Biville; Anchun Cheng (Current Microbiology, 2016)

Identification and molecular characterization of a novel duck Tembusu virus isolate from Southwest China - Kesen Zhu; Juan Huang; Renyong Jia; Bin Zhang; Mingshu Wang; Dekang Zhu; Shun Chen; Mafeng Liu; Zhongqiong Yin; Anchun Cheng (Archives of Virology, 2015)

Pectin Modifications: A Review - Jun Chen; Wei Liu; Cheng-Mei Liu; Ti Li; Rui-Hong Liang; Shun-Jing Luo (Critical Reviews in Food Science and Nutrition, 2015)

Ecotoxicity of two organophosphate pesticides chlorpyrifos and dichlorvos on non-targeting cyanobacteria Microcystis wesenbergii - Kai-Feng Sun; Xiang-Rong Xu; Shun-Shan Duan; You-Shao Wang; Hao Cheng; Zai-Wang Zhang; Guang-Jie Zhou; Yi-Guo Hong (Ecotoxicology, 2015)

Contrasting effects of ammonium and nitrate inputs on soil CO2 emission in a subtropical coniferous plantation of southern China - Yongsheng Wang; Shulan Cheng; Huajun Fang; Guirui Yu; Xiaofeng Xu; Minjie Xu; Lei Wang; Xiaoyu Li; Gaoyue Si; Jing Geng; Shun He (Biology and Fertility of Soils, 2015)

Preparation of TiO2/Silicalite-2@CoFe2O4 Magnetic Composites and Evaluation of their Photocatalytic Activity in Cr(VI) Removal - Mang Lu; Yue Cheng; Shun-long Pan; Ting-ling Yang; Zhong-zhi Zhang (Water, Air, & Soil Pollution, 2015)

Metamorphic P-T trajectory and multi-stage fluid events of vein-bearing UHP eclogites from the Dabie terrane: insights from compositional zonations of key minerals - Shun Guo; Kai Ye; Nanfei Cheng; Yi Chen; Bin Su; Jingbo Liu (International Geology Review, 2015)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

Quercetin induces mitochondrial-derived apoptosis via reactive oxygen species-mediated ERK activation in HL-60 leukemia cells and xenograft - Wei-Jiunn Lee; Michael Hsiao; Junn-Liang Chang; Shun-Fa Yang; Tsui-Hwa Tseng; Chao-Wen Cheng; Jyh-Ming Chow; Ke-Hsun Lin; Yung-Wei Lin; Chung-Chi Liu; Liang-Ming Lee; Ming-Hsien Chien (Archives of Toxicology, 2015)

Complete genome sequence of a new recombinant echovirus 25 strain isolated from a neonatal patient with hand, foot, and mouth disease complicated by encephalitis in Beijing, China - Hongjie Li; Yixing Meng; Lin Pang; Jinqiu Liang; Hongping Lu; Qi Wang; Pu Liang; Jinfeng Cao; Shun-ai Liu; Jun Cheng (Virus Genes, 2015)

Protection of Facial Nerves During Acoustic Neuroma Surgery - Hong-shun Xing; Shou-xian Wang; Zhe Wang; Pei-cheng Cao; Yong-qian Ma; Zeng-wu Wang (Cell Biochemistry and Biophysics, 2015)

Geochronological and geochemical constraints on the petrogenesis and geodynamic setting of the Qianlishan granitic pluton, Southeast China - Chun-Li Guo; Ru-Cheng Wang; Shun-Da Yuan; Sheng-Hua Wu; Bing Yin (Mineralogy and Petrology, 2015)

Partial Volume Correction for Equivocal Retropharyngeal Nodal Metastases of Nasopharyngeal Carcinoma with Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography - Yu-Wen Wang; Chin-Shun Wu; Chih-Han Chang; Kuo-Sheng Cheng; Yu-Kang Chang; I-Wen Huang; Chin-Li Lu; Wei-Jen Yao (Journal of Medical and Biological Engineering, 2015)

Early-life sleep deprivation persistently depresses melatonin production and bio-energetics of the pineal gland: potential implications for the development of metabolic deficiency - Li-You Chen; Cheng Tiong; Chung-Hung Tsai; Wen-Chieh Liao; Shun-Fa Yang; Su-Chung Youn; Fu-Der Mai; Hung-Ming Chang (Brain Structure and Function, 2015)

Suppression of PI3K/Akt signaling by synthetic bichalcone analog TSWU-CD4 induces ER stress- and Bax/Bak-mediated apoptosis of cancer cells - Meng-Liang Lin; Shih-Shun Chen; Ren-Yu Huang; Yao-Cheng Lu; Yu-Ren Liao; Mopuru Vijaya Bhaskar Reddy; Chuan-Chun Lee; Tian-Shung Wu (Apoptosis, 2014)

Nest defenses and egg recognition of yellow-bellied prinia against cuckoo parasitism - Canchao Yang; Longwu Wang; Shun-Jen Cheng; Yu-Cheng Hsu; Wei Liang; Anders Pape Møller (The Science of Nature, 2014)

Cloning, expression and purification of duck hepatitis B virus (DHBV) core protein and its use in the development of an indirect ELISA for serologic detection of DHBV infection - Qiang Liu; Renyong Jia; Mingshu Wang; Juan Huang; Dekang Zhu; Shun Chen; Zhongqiong Yin; Yin Wang; Xiaoyue Chen; Anchun Cheng (Archives of Virology, 2014)

Comparative gut transcriptome analysis reveals differences between virulent and avirulent Russian wheat aphids, Diuraphis noxia - Radhika Anathakrishnan; Deepak K. Sinha; Marimuthu Murugan; Kun Yan Zhu; Ming-Shun Chen; Yu Cheng Zhu; C. Michael Smith (Arthropod-Plant Interactions, 2014)

Low Glucose Utilization and Neurodegenerative Changes Caused by Sodium Fluoride Exposure in Rat’s Developmental Brain - Chunyang Jiang; Shun Zhang; Hongliang Liu; Zhizhong Guan; Qiang Zeng; Cheng Zhang; Rongrong Lei; Tao Xia; Zhenglun Wang; Lu Yang; Yihu Chen; Xue Wu; et al. (NeuroMolecular Medicine, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Construction and identification of a cDNA library for use in the yeast two-hybrid system from duck embryonic fibroblast cells post-infected with duck enteritis virus - Xinghong Gao; Renyong Jia; Mingshu Wang; Dekang Zhu; Shun Chen; Meng Lin; Zhongqiong Yin; Yin Wang; Xiaoyue Chen; Anchun Cheng (Molecular Biology Reports, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Local scour and the laws of scour pit’s shape downstream of debris flow sabo dam - Hua-li Pan; Shun Yang; Guo-qiang Ou; Jiang-cheng Huang (Journal of Mountain Science, 2013)

α-Mangostin induces mitochondrial dependent apoptosis in human hepatoma SK-Hep-1 cells through inhibition of p38 MAPK pathway - Shu-Ching Hsieh; Min-Hsien Huang; Chun-Wen Cheng; Jyun-Hao Hung; Shun-Fa Yang; Yi-Hsien Hsieh (Apoptosis, 2013)

The transcription analysis of duck enteritis virus UL49.5 gene using real-time quantitative reverse transcription PCR - Meng Lin; Renyong Jia; Mingshu Wang; Xinghong Gao; Dekang Zhu; Shun Chen; Zhongqiong Yin; Yin Wang; Xiaoyue Chen; Anchun Cheng (Virus Genes, 2013)

Genesis and evolution of subduction-zone andesites: evidence from melt inclusions - Ming-Shuai Zhu; Lai-Cheng Miao; Shun-Hu Yang (International Geology Review, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Biocatalytic characterization of a short-chain alcohol dehydrogenase with broad substrate specificity from thermophilic Carboxydothermus hydrogenoformans - Shuo Zhou; Shun-Cheng Zhang; Dun-Yue Lai; Shuang-Ling Zhang; Zhen-Ming Chen (Biotechnology Letters, 2013)

Investigation of transferability of BovineSNP50 BeadChip from cattle to water buffalo for genome wide association study - Jun Jing Wu; Li Jun Song; Fang Jie Wu; Xian Wei Liang; Bing Zhuang Yang; D. Claire Wathes; Geoff E. Pollott; Zhangrui Cheng; De Shun Shi; Qing You Liu; Li Guo Yang; Shu Jun Zhang (Molecular Biology Reports, 2013)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

A review of the pharmacological effects of Arctium lappa (burdock) - Yuk-Shing Chan; Long-Ni Cheng; Jian-Hong Wu; Enoch Chan; Yiu-Wa Kwan; Simon Ming-Yuen Lee; George Pak-Heng Leung; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2011)

Evaluation of surfactants as solubilizing agents in microsomal metabolism reactions with lipophilic substrates - Kathleen Randall; Shun Wen Cheng; Anne Therese Kotchevar (In Vitro Cellular & Developmental Biology - Animal, 2011)

Effects of Copper Exposure on Expression of Glutathione-Related Genes in Acidithiobacillus ferrooxidans - Jin-lan Xia; Shun Wu; Rui-yong Zhang; Cheng-gui Zhang; Huan He; Hong-chen Jiang; Zhen-yuan Nie; Guan-zhou Qiu (Current Microbiology, 2011)

Acacetin inhibits the invasion and migration of human non-small cell lung cancer A549 cells by suppressing the p38α MAPK signaling pathway - Shang-Tao Chien; Su-Shun Lin; Cheng-Kun Wang; Yuan-Bin Lee; Kun-Shiang Chen; Yao Fong; Yuan-Wei Shih (Molecular and Cellular Biochemistry, 2011)

Positive sampling artifacts in particulate organic carbon measurements in roadside environment - Yan Cheng; Shun Cheng Lee; Kin Fai Ho; Kochy Fung (Environmental Monitoring and Assessment, 2010)

Season variations for metallic elements compositions study in plant Bidenens pilosa L. var. radiate Sch. in central Taiwan - Yuh-Shen Wu; Guor-Cheng Fang; Shun-Hisu Lin (Environmental Monitoring and Assessment, 2010)

Homocysteine enhances cell proliferation in hepatic myofibroblastic stellate cells - Cheng-Gang Zou; Shun-Yu Gao; Yue-Shui Zhao; Shu-De Li; Xiu-Zhen Cao; Yan Zhang; Ke-Qin Zhang (Journal of Molecular Medicine, 2009)

Differential Responses of Wheat Inhibitor-like Genes to Hessian Fly, Mayetiola destructor, Attacks During Compatible and Incompatible Interactions - Junxiang Wu; Xuming Liu; Shize Zhang; Yu-Cheng Zhu; R. Jeffrey Whitworth; Ming-Shun Chen (Journal of Chemical Ecology, 2008)

Polymorphism for Transforming Growth Factor Beta 1-509 (TGF-B1-509): Association with Endometriosis - Yao-Yuan Hsieh; Chi-Chen Chang; Fuu-Jen Tsai; Ching-Tien Peng; Lian-Shun Yeh; Cheng-Chieh Lin (Biochemical Genetics, 2005)

Eudragit E Accelerated the Diketopiperazine Formation of Enalapril Maleate Determined by Thermal FTIR Microspectroscopic Technique - Shun-Li Wang; Shan-Yang Lin; Ting-Fang Chen; Wen-Ting Cheng (Pharmaceutical Research, 2004)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)

Reduced vascular β-adrenergic receptors and catecholamine response in rats with lead induced hypertension - Huoy-Rou Chang; Shun-Sheng Chen; Der-An Tsao; Juei-Tang Cheng; Chi-Kung Ho; Hsin-Su Yu (Archives of Toxicology, 1997)